(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
In 1967, on the occasion of the quadricentennial of the Hispanic foundation of the city of Caracas, the Círculo Musical published a special edition entitled Caracas 400 años. Several volumes beautifully designed, among others, by Godo Romero and J. E. Franco, and printed in the workshops of Tecnocolor and Selecolor. The illustrations were done by painter Virgilio Trómpiz and the photographs are by Mauro Rodríguez and Gilberto Fuentes. The collection, a multimedia work of its time, has several discs, some of them entitled: “Pensamiento político del Libertador”, “Música colonial venezolana”, “Música venezolana de concierto”, “La música del siglo XIX”, “Música popular” (3 LPs), “Valores literarios” and “El teatro en Venezuela”.